Case series report of navigation-based in vivo knee kinematics in total knee arthroplasty with a gradually reducing femoral radius design. (May 2017) - Takagi, Hiroshi; Asai, Soshi; Sato, Atsushi; Maekawa, Masahiko; Kawashima, Humiyoshi; Kanzaki, Koji
Abstract: Background: Simulations show that paradoxical anterior femoral slide in conventional dual radius total knee arthroplasty (TKA) is initiated by sudden reduction of the femoral radius from distal to posterior. Therefore, we hypothesized that a new TKA prosthesis design with a gradually reducing femoral radius may minimize the anterior slide in navigation-based in vivo knee kinematics. The purpose of this study was to compare the kinematics of TKA in vivo using a prosthesis with a gradually reducing radius, in comparison with the conventional dual radius design. Methods: A retrospective case series report was performed for 12 knees with osteoarthritis using a CT-free navigation system. Six knees received TKA using a prosthesis with a gradually reducing femoral radius (Attune CR) and the other 6 knees underwent TKA using a conventional dual radius design (PFCΣ CR). Anterior-posterior (AP) displacement of the medial and lateral femoral condyles relative to the tibia, and kinematic patterns of the femur throughout the range of motion were compared between the groups. Results: The average AP displacement in the Attune CR group indicated no paradoxical anterior movement of both condyles, and kinematic data showed a medial pivot pattern. In contrast, AP displacement in the PFCΣ CR group indicated that both condyles showed paradoxical anterior movement, and kinematically both condyles moved in the same manner, showing a parallel motion pattern. Conclusion: TKA using a prosthesis with a gradually reducing radius minimized paradoxical anterior slide in navigation-based in vivo knee kinematics. Highlights: The case series of TKA using a prosthesis with a gradually reducing radius by navigation system was performed. TKA with a gradually reducing femoral radius minimized paradoxical anterior slide in navigation-based in vivo knee kinematics. The kinematic pattern was a medial pivot pattern using a prosthesis with a gradually reducing radius.